Isiris™: A New Single Use Digital Cystoscope For Double-J Stent Removal - Tarık Emre Şener; Michele Talso; Esteban Emiliani; Laurian Dragos; Salvatore Butticè; Yılören Tanıdır (Journal of Urological Surgery, 2019)

(untitled)
Isiris™ (Porgès-Coloplast) is a single-use digital flexible cystoscope, with an integrated grasper approved for double-J stent removal with comparable characteristics with other digital cystoscopes in the market. Isiris has its own monitor that can be mounted anywhere; and also with an integrated camera and a grasper system, stent removal can be performed at any place without any time restriction and also without a delay between two procedures. Isiris provides the use of a brand-new device in each procedure without a risk of contamination. The digital image quality and easy maneuverability and the potential cost reduction with a single-use device are the advantages, which all urologists should appreciate.